Mediation Of Customer Service in The Relation to Trust and Service Culture's Impact on Customer Satisfaction At PT. Asuransi Raksa Pratikara in Bandung - Yanti Yulansari, Gusti Ayu Komang; Sinaga, Firman; Suadnyana, I Wayan; Shanty Muni Parwati, Komang; Lannovia Amir , Firlie; Yoga Kharisma Pradana, Gede (International Journal of Accounting and Economics Studies, 2025)
This study aims to examine the correlation of trust, service culture, and customer service concerning consumer satisfaction. Trust is an essential element of service culture for attaining client happiness in the insurance industry. Client service is a fundamental element of the service culture that influences trust and client satisfaction with their insurance. It is significant to assess customer confidence and satisfaction with the customer service function at PT. Asuransi Raksa Pratikara in Bandung seems to lack credibility. The study was conducted using quantitative methods. We acquired primary data through a questionnaire survey. We enhanced the dataset using more data obtained from a literature review. All data were analyzed inferentially using Structural Equation Modeling with Partial Least Squares (SEM PLS). The results indicate that the service culture favorably affects customer satisfaction (H1) and that feelings of comfort, safety, and confidence during interactions with the business enhance consumer contentment (H4). The company's failure to promptly address customer issues and effectively resolve problems that diminish customer satisfaction, coupled with a lack of swift responses in customer service regarding requests or complaints, can adversely affect customer satisfaction at PT Asuransi Raksa Pratikara in Bandung.
Keywords: Trust, Service Culture, Customer Service, Insurance Customer Satisfaction, PT Asuransi Raksa Pratikara, Bandung